2007
DOI: 10.1074/jbc.m705095200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel N-terminal Isoform of the Neuron-specific K-Cl Cotransporter KCC2

Abstract: The neuronal K-Cl cotransporter KCC2 maintains the low intracellular chloride concentration required for the hyperpolarizing actions of inhibitory neurotransmitters ␥-aminobutyric acid and glycine in the central nervous system. This study shows that the mammalian KCC2 gene (alias Slc12a5) generates two neuron-specific isoforms by using alternative promoters and first exons. The novel KCC2a isoform differs from the only previously known KCC2 isoform (now termed KCC2b) by 40 unique N-terminal amino acid residues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
160
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(174 citation statements)
references
References 34 publications
13
160
1
Order By: Relevance
“…The available data indicate that the latter isoform is required for the developmental E GABA shift, but little is known about the functional significance of KCC2a (Uvarov et al, 2007(Uvarov et al, , 2009). Nevertheless, the parallel activitydependent upregulation of the two isoforms is interesting because of their capability of heterodimerization (Uvarov et al, 2009 Ϫ extrusion mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The available data indicate that the latter isoform is required for the developmental E GABA shift, but little is known about the functional significance of KCC2a (Uvarov et al, 2007(Uvarov et al, , 2009). Nevertheless, the parallel activitydependent upregulation of the two isoforms is interesting because of their capability of heterodimerization (Uvarov et al, 2009 Ϫ extrusion mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…2 E-G). Two splice variants of KCC2 (KCC2a and b) have recently been described (Uvarov et al, 2007). These isoforms are coexpressed in most brain regions and seem to be able to form heterodimers (Uvarov et al, 2009).…”
Section: B the Increase In The CLmentioning
confidence: 99%
“…The shift in polarity of GABA A responses occurs in rodent hippocampus during the first 2 postnatal weeks (Farrant and Kaila, 2007). We have shown that the KCC2 gene generates two isoforms, KCC2a and KCC2b, by an alternative promoter and first exon usage (Uvarov et al, 2007). During development, expression levels of KCC2a mRNA in hippocampus are relatively constant, whereas KCC2b mRNA increases significantly.…”
Section: Introductionmentioning
confidence: 97%
“…During development, expression levels of KCC2a mRNA in hippocampus are relatively constant, whereas KCC2b mRNA increases significantly. This indicates that the developmental increase in the expression of KCC2 mRNA and protein is mainly due to the KCC2b isoform (Uvarov et al, 2007(Uvarov et al, , 2009.…”
Section: Introductionmentioning
confidence: 97%
“…KCC2a (26) was obtained by cutting and pasting KCC2 exon 1a amplified from the human fetal brain cDNA library in a process similar to that described above. KCC2a construction was verified by DNA sequencing.…”
Section: Clones Cloning and Sequencingmentioning
confidence: 99%